(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This article is about women writers who created works of art in network literature, which is a new phenomenon. In contemporary Chinese literature, as in other fields, the Internet has become an enabling tool for migrant workers, the disabled with varying degrees of mobility, and the wealthy millionaires alike. The trend of feminist thinking has helped to improve the social living status of women. Women are struggling to make their voices heard on all fronts and to explore the new meaning of ‘gender equality’. This research is also reflected in literary creation. With the rapid development of computer and network technologies, the creation and distribution of literary works, the transition from paper media to online media has greatly accelerated the process. In contrast to the dominance of men in the traditional literature, it can be seen that the position of women in the Chinese network literature is relatively elevated, and even tends to dominate in some respects. The TV series and films that have caused a great deal of interest over the past two years are the works of female artists who have been working in the field of literature.